Development of active & passive airborne remote sensors - Kanisin, Devaraj; Shokouhi, Mohammad; Wong, Wai Pun; Singh, Manveer; Siau, Wing Ket; Tang, Sai Hong; Ismail, Napsiah (2005)
The paper presents about the development of advance airborne remote sensors. There are two types of remote sensors, which are active sensor and passive sensor. The active sensor records the reflected electromagnetic energy from the surface of the Earth or the target. It produce its own source of electromagnetic energy to emit. While the passive sensor works similarly but it dependent on the Sun as the source of electromagnetic energy. The active sensor is known as Synthetic Aperture Radar (SAR). It is a microwave imaging technology which collects data using L-band (1250 MHz). SAR system is a 24 hours operational system as it is independent of the source of the light and also the weather. The SAR system can also obtain high resolution two-dimensional image. The passive sensor is a high spectral resolution airborne optical mechanical scanning imaging spectrometer (OMSIS). It is a hyperspectral imaging sensor which collects data over variety of different spectral bands, from visible to thermal infrared. It is a 68 band configuration systems. Both the remote sensor can be used for the environment studies and investigation, disaster management, urban planning, agriculture application, etc.